Interactions between Myc and Mediators of Inflammation in Chronic Liver Diseases - Ting Liu; Yu Zhou; Kwang Suk Ko; Heping Yang (Hindawi Limited, 2015)
Most chronic liver diseases (CLDs) are characterized by inflammatory processes with aberrant expressions of various pro- and anti-inflammatory mediators in the liver. These mediators are the driving force of many inflammatory liver disorders, which often result in fibrosis, cirrhosis, and liver tumorigenesis. c-Myc is involved in many cellular events such as cell growth, proliferation, and differentiation. c-Myc upregulates IL-8, IL-10, TNF-α, and TGF-β, while IL-1, IL-2, IL-4, TNF-α, and TGF-β promote c-Myc expression. Their interactions play a central role in fibrosis, cirrhosis, and liver cancer. Molecular interference of their interactions offers possible therapeutic potential for CLDs. In this review, current knowledge of the molecular interactions between c-Myc and various well known inflammatory mediators is discussed.